Tripticks - Quin, Ann 1936-1973 (Dalkey Archive Press, 2002)
"Ann Quin's Tripticks offers an episodic account of the narrator's flight across a surreal American landscape, pursued by his "No. 1 X-wife" and her new lover. This masterpiece of pre-punk aesthetics critiques the hypocrisy and consumerism of modern culture while spoofing the 'typical' maladjusted family, which in this case includes a father who made his money in ballpoint pens and a mother whose life revolves around her overpampered, all-demanding poodle."--BOOK JACKET.